Influence of period-doubling bifurcations in the appearance of border collisions for a ZAD-strategy-controlled buck converter - D'amico, Edith Maria Belen (2012)
The first period-doubling bifurcation of a dc-dc buck converter controlled by a zero-average dynamic strategy is studied in detail. Owing to the saturation of the duty cycle, this bifurcation is followed by a border-collision bifurcation, which is the main mechanism to introduce instability and chaos in the circuit. The multiparameter analysis presented here leads to a complete knowledge of the relatioship between these two bifurcations. The results are obtained by using a frequency-domain approach for the study of period-two oscillations in maps. © 2010 John Wiley & Sons, Ltd.